Deriving pre-eutrophic conditions from an ensemble model approach for the North-West European seas - Sonja M. van Leeuwen; Hermann-J. Lenhart; Theo C. Prins; Anouk Blauw; Xavier Desmit; Liam Fernand; Rene Friedland; Onur Kerimoglu; Genevieve Lacroix; Annelotte van der Linden; Alain Lefebvre; Johan van der Molen; et al. (Frontiers in Marine Science, 2023)
The pre-eutrophic state of marine waters is generally not well known, complicating target setting for management measures to combat eutrophication. We present results from an OSPAR ICG-EMO model assessment to simulate the pre-eutrophic state of North-East Atlantic marine waters. Using an ecosystem model ensemble combined with an observation-based weighting method we derive sophisticated estimates for key eutrophication indicators. Eight modelling centres applied the same riverine nutrient loads, atmospheric nutrient deposition rates and boundary conditions to their specific model set-up to ensure comparability. The pre-eutrophic state was defined as a historic scenario of estimated nutrient inputs (riverine, atmospheric) at around the year 1900, before the invention and widespread use of industrial fertilizers. The period 2009-2014 was used by all participants to simulate both the current state of eutrophication and the pre-eutrophic scenario, to ensure that differences are solely due to the changes in nutrient inputs between the scenarios. Mean values were reported for winter dissolved inorganic nutrients and total nutrients (nitrogen, phosphorus) and the nitrogen to phosphorus ratio, and for growing season chlorophyll, chlorophyll 90 th percentile, near-bed oxygen minimum and net phytoplankton production on the level of the OSPAR assessment areas. Results showed distinctly lower nutrient concentrations and nitrogen to phosphorus ratio’s in coastal areas under pre-eutrophic conditions compared to current conditions (except in the Meuse Plume and Seine Plume areas). Chlorophyll concentrations were estimated to be as much as ~40% lower in some areas, as were dissolved inorganic phosphorus levels. Dissolved inorganic nitrogen levels were found to be up to 60% lower in certain assessment areas. The weighted average approach reduced model disparities, and delivered pre-eutrophic concentrations in each assessment area. Our results open the possibility to establish reference values for indicators of eutrophication across marine regions. The use of the new assessment areas ensures local ecosystem functioning is better represented while political boundaries are largely ignored. As such, the reference values are less associated to member states boundaries than to ecosystem boundaries.

Corrigendum: Advection and composition of Dinophysis spp. populations along the European Atlantic shelf - Saeed Hariri; Martin Plus; Mickael Le Gac; Véronique Séchet; Marta Revilla; Marc Sourisseau (Frontiers in Marine Science, 2022)

Advection and Composition of Dinophysis spp. Populations Along the European Atlantic Shelf - Saeed Hariri; Martin Plus; Mickael Le Gac; Véronique Séchet; Marta Revilla; Marc Sourisseau (Frontiers in Marine Science, 2022)
The main objective was to study relationships between the regional biogeography of Dinophysis species and water masses circulation along the European Atlantic coast. Hydrodynamic connectivities were estimated with a Lagrangian approach. Available and validated physical hindcasts from regional hydrodynamical models, with different resolutions were used. The target area is the Bay of Biscay (NE Atlantic) and connectivity was evaluated between a set of spatially distributed stations and during temporally specified periods. Different indexes related to connectivity properties such as mean, median, most frequent transit times were calculated. To illustrate the dispersion pattern, a molecular approach was jointly set-up to describe the species composition of this genus. At the seasonal scale, a high connectivity within the Bay of Biscay was observed with a slight northward connectivity from Galicia coastal waters to the Shelf of the Bay of Biscay. By comparison to the connectivity between shelf waters of French Brittany and English Channel waters, a higher connectivity between shelf waters of French Brittany and the Celtic Sea shelf was observed. The species mixing in the Bay of Biscay from Galicia waters to the Celtic Sea was confirmed by the genetic analyses despite the absence of Dinophysis sacculus in natural samples. The molecular methodology developed for this work, permitting at least the description of the species composition, also highlights, at the European scale, an unexpected low genetic variability which echoes the complex taxonomic classification inside the genus and the difficulties encountered by national monitoring programs to reach a taxonomic resolution at species level. It is now necessary to start some monitoring at the species level before realizing mid- or long-term forecasts.

Current distribution and potential expansion of the harmful benthic dinoflagellate Ostreopsis cf. siamensis towards the warming waters of the Bay of Biscay, North‐East Atlantic - Kévin Drouet; Cécile Jauzein; Dominique Herviot‐Heath; Saeed Hariri; Aitor Laza‐Martinez; Cyrielle Lecadet; Martin Plus; Sergio Seoane; Marc Sourisseau; Rodolphe Lemée; Raffaele Siano (Environmental Microbiology, 2021)
Summary In a future scenario of increasing temperatures in North‐Atlantic waters, the risk associated with the expansion of the harmful, benthic dinoflagellate Ostreopsis cf. siamensis has to be evaluated and monitored. Microscopy observations and spatio‐temporal surveys of environmental DNA (eDNA) were associated with Lagrangian particle dispersal simulations to: (i) establish the current colonization of the species in the Bay of Biscay, (ii) assess the spatial connectivity among sampling zones that explain this distribution, and (iii) identify the sentinel zones to monitor future expansion. Throughout a sampling campaign carried out in August to September 2018, microscope analysis showed that the species develops in the south‐east of the bay where optimal temperatures foster blooms. Quantitative PCR analyses revealed its presence across almost the whole bay to the western English Channel. An eDNA time‐series collected on plastic samplers showed that the species occurs in the bay from April to September. Due to the water circulation, colonization of the whole bay from the southern blooming zones is explained by inter‐site connectivity. Key areas in the middle of the bay permit continuous dispersal connectivity towards the north. These key areas are proposed as sentinel zones to monitor O . cf. siamensis invasions towards the presumably warming water of the North‐East Atlantic.

Submerged benthic macrophytes in Mediterranean lagoons: distribution patterns in relation to water chemistry and depth - Ines Le Fur; Rutger De Wit; Martin Plus; Jocelyne Oheix; Monique Simier; Vincent Ouisse (Hydrobiologia, 2018)

Resource Competition Affects Plankton Community Structure; Evidence from Trait-Based Modeling - Marc Sourisseau; Valerie Le Guennec; Guillaume Le Gland; Martin Plus; Annie Chapelle (Frontiers in Marine Science, 2017)

Modelling the effects of Zostera noltei meadows on sediment dynamics: application to the Arcachon lagoon - Katerina Kombiadou; Florian Ganthy; Romaric Verney; Martin Plus; Aldo Sottolichio (Ocean Dynamics, 2014)

Environmental factors contributing to the development of brown muscle disease and perkinsosis in M anila clams ( R uditapes philippinarum ) and trematodiasis in cockles ( C erastoderma edule ) of A rcachon B ay - Cindy Binias; Van Tu Do; Florence Jude‐Lemeilleur; Martin Plus; Jean‐Marie Froidefond; Xavier de Montaudouin (Marine Ecology, 2014)
The aim of the present study was to identify environmental factors that could explain the distribution of different pathologies of commercially exploited intertidal bivalves in an Atlantic lagoon, Arcachon Bay. In particular, the role of the salinity gradient as a driver was explored. The Manila clam Ruditapes philippinarum experienced two severe pathologies, perkinsosis, which is due to a protozoan parasite, and brown muscle disease ( BMD ), the etiological agent of which remains unknown. Perkinsus olseni infection was very low in a small low‐salinity area but, at the scale of the entire lagoon, was more influenced by organic matter content in the sediment and by emersion time. BMD prevalence was also 2.6 times higher in the higher organic content area but was also negatively correlated with salinity. The sympatric cockle ( Cerastoderma edule ) was affected by eight trematode species. These parasites have a complex life cycle that generally involves three free‐living host species. The distribution of the different trematode communities was rather patchy within Arcachon Bay with no clear relationship with measured environmental factors. The dominance of particular trematode species could be due to the presence of other hosts involved in their life cycle, making it more difficult to detect a major environmental driver. This survey demonstrated that salinity is not a major factor explaining disease distribution in this temperate lagoon. This result has consequences for the research of ‘refuge areas’ (free of diseases) or ‘hot spots’ (heavy infection) for species of high economic value.